Identificação molecular de espécies do gênero cichla (cichliformes: Cichlidae) Introduzidas em bacias hidrográficas maranhenses - Almeida, Marcelo Silva de (2022)
The inference on the origin of fish stocks introduced outside their habitat with a phylogenetic approach constitutes an important step in understanding and controlling the expansion of invasive species. In this sense, we used the DNA barcoding technique to identify species of the genus Cichla in Maranhão basins. The fish were collected in the Mearim/tributaries, Pindaré, Parnaíba and Tocantins basins, using nets of gillnets and nets, and then transported to the Laboratory of Genetics and Molecular Biology (GENBIMOL) for sorting and identification with the aid of specific literature and submitted to DNA extraction techniques, COI gene amplification via PCR and sequencing. Editing, sequence alignment, genetic distances, haplotype network were performed using the BioEdit, MEGA X and Network programs. ABGD, ASAP GYMC and PTP models were used for OTU delimitation. A total of 78 sequences of the COI gene were obtained, 37 sequences correspond to the species Cichla kelberi from the Pindaré River, Cichla monoculus from the Flores River, Cichla piquiti from the Tocantins River and Cichla sp. from the Parnaíba river and 41 sequences were from Genbank, with average intraspecific genetic divergence of 0% and interspecific genetic divergence from 6.78% to 44.75%. The clusters by phylogenetic reconstructions of (ML) and (BI) showed strongly supported clades, indicating agreement with the species assigned by morphological identification. A total of six haplotypes were obtained for specimens of the genus Cichla, with haplotypic diversity values h= 0.726 and nucleotide diversity π= 0.0479. The H1 haplotype was shared in populations of C. monoculus from the Parnaíba, Mearim and Alto Paraná rivers. The H2 haplotype shared populations of C. kelberi from the Pindaré, Tocantins and Alto Paraná rivers. The H3 haplotype was shared with populations of C. piquiti from the Tocantins and Paraná rivers. Three exclusive haplotypes were observed for the populations of Cichla ocellaris from the Maroni River in French Guiana, for Cichla melaniae and Cichla mirianae from the Xingú (H4, H5 and H6). The identification performed on the BOLD Systems platform confirmed the morphological identification of the species under study with a similarity of 99.13 to 100%. Therefore, we suggest that specimens of C. kelberi from the Pindaré River come from native populations from the Tocantins River basin and C. monoculus from the Mearim, Parnaíba and Alto Paraná Rivers, as they constitute the same haplotype, come from the same stock. It is also possible to infer that C. piquiti from the Paraná River is derived from populations from the Tocantins River. In conclusion, our study was the first to use molecular analysis to validate the presence of C. monoculus as an invasive species in Maranhão rivers, as well as confirming the introduction and registration of C. kelberi in the Pindaré River